Interactive responses of root and shoot of camphor tree (Cinnamomum camphora L.) to asymmetric disturbance treatments - Wang, Hongbing; Hu, Yonghong; Qin, Jun; Guo, Chenbing; Wu, Duorun; Xing, Qiang; Pan, Lianlian; Xia, Kangsheng; Shen, Yajun; Guo, Jingjing; Jiang, Ran (Frontiers in Plant Science, 2022)
Plant root and shoot growth are closely interrelated, though the connotation of root–shoot balance should not be limited to their connectivity in biomass and physiological indicators. Their directional distribution of mass in architecture and the resulting root–shoot interactions are the keys to understanding the dynamic balance of the below- and above-ground organs related to tree anchorage. This study focuses on the 4-year-old camphor tree (Cinnamomum camphora L.) as a system to observe the biomass distribution in response to the asymmetric disturbance treatments of biased root (BRT), inclined trunk (ITT), and half-crown (HCT) in a controlled cultivation experiment using the minirhizotron technique. We found an inverse relationship of biomass distribution of crowns to roots in BRT and opposite asymmetries of roots with crowns in response to the ITT and HCT treatments. We also observed higher net photosynthesis rate (Pn), water use efficiency, and chlorophyll content in the leaves on the side opposite the lean in ITT, and higher Pn, transpiration rate, and chlorophyll content on the root-bias side in BRT, which is consistent with the nutrient allocation strategies of allocating nutrients across plant organs in an optimal way to obtain ‘functional equilibrium’ and adapt to the stressed environment. Furthermore, the asymmetrical growth transformation of first-level branch length from the root-bias side to the opposite side in BRT, and a similar transformation of root length from the crown-bias side to the opposite side in HCT, imbues further theoretical support of the nutrient allocation strategy and the biomechanical stability principle, respectively. In summary, this study is the first to identify opposite interaction between below- and above-ground biomass distributions of the camphor tree. The findings enrich the connotation of root–shoot interactions and help to realize root design for the silviculture management of urban forests.